'Professional-supportive' versus 'economic-operational' management: the relationship between leadership style and hospital physicians' organisational climate - Pål E. Martinussen; Tonje Davidsen (BMC, 2021)
Abstract Background Health systems across the world have implemented reforms that call for a reconsideration of the role of management in hospitals, which is increasingly seen as important for performance. These reorganisation efforts of the hospitals have challenged and supplemented traditional profession-based management with more complex systems of management inspired by the business sector. Whereas there is emerging evidence on how medical professionals in their role as leaders and managers adapt to the new institutional logics of the health care sector with increasing demands for efficiency and budgetary discipline, no previous studies have investigated whether leaders' emphasis on clinical or financial priorities is related to how hospital physicians' view their working situation. The purpose of this study was therefore to examine the relationship between leadership style and hospital physicians' organisational climate. Methods We utilised data from a survey among 3000 Norwegian hospital physicians from 2016. The analysis used three additive indexes as dependent variables to reflect various aspects of the organisational climate: social climate, innovation climate and engagement at the workplace. The variables reflecting leadership style were based on an item in the survey asking the respondents to rate the leadership qualities of their proximate leaders (department chair) on 11 specific dimensions. We used factor analysis to identify two types of leadership styles: a traditional profession-based leadership style that emphasises the promotion of professional standards and quality in patient treatment, and a leadership style that reflects the emerging management philosophy with focus on economic administration and budgetary control. Controlling for demographic background, leader role, foreign medical exam and specialty, the empirical model was estimated via multivariate regression. Results The results documented a clear relationship between leadership style and organisational climate: a 'professional-supportive' leadership style is associated with better social climate, innovation climate and engagement at the workplace, while an 'economic-operational' leadership style is associated with a poorer social climate. Conclusions The cross-sectional study design makes it impossible to draw inferences about direction of causality and causal pathways. However, the positive relationship between professional-supportive leadership and organisational climate is a matter, which should be seriously considered regardless of direction of causality.